2008
DOI: 10.1007/s12011-008-8109-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin E and Selenium on Serum Trace and Major Elements in Horses

Abstract: The combined effects of vitamin E and selenium were studied in native Anatolian horses subject to strenuous exercise. The concentrations of copper, zinc, iron, calcium, potassium, and magnesium were determined in serum by atomic absorption spectrometry in two study groups (n = 25 each), one of which served as untreated controls. After exercising the horses by running 1,500 m in about 7 min, only the copper level and the copper/zinc ratio significantly increased (p < 0.05), but the concentrations of calcium, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
1
12
0
4
Order By: Relevance
“…Estudos têm associado a elevação nos níveis de Fe e Cu em equinos da raça PSI (Balarin 2002) e Anatoliano nativo (Yur et al 2008), decorrente do exercício físico. A contração esplênica e a hemoconcentração provocada pela sudorese deve ter promovido a elevação sérica de Fe e Cu observada no presente estudo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estudos têm associado a elevação nos níveis de Fe e Cu em equinos da raça PSI (Balarin 2002) e Anatoliano nativo (Yur et al 2008), decorrente do exercício físico. A contração esplênica e a hemoconcentração provocada pela sudorese deve ter promovido a elevação sérica de Fe e Cu observada no presente estudo.…”
Section: Discussionunclassified
“…O interesse em avaliar ferro, cobre, zinco e manganês, relacionando-os com exercício baseia-se no fato de que estes minerais participam do metabolismo oxidativo e destruição dos peróxidos, tendo uma relação estreita na capacidade de oxigenação dos pulmões, no trabalho cardiovascular e no desempenho físico dos animais (Yur et al 2008).…”
Section: Introductionunclassified
“…Because of the low number of specimens, differences were not statistically evaluated. Table 9 provides a comparison of concentrations of zinc and copper with values reported for the domestic horse (Grace et al 1999;Ayetkin et al 2010;Yur et al, 2008).…”
Section: Haematological Parametersmentioning
confidence: 99%
“…Similarly, in serum the increased values of Cu after training, with a simultaneous significant decrease of Zn and Mn levels, were observed by Minini et al (2013). Yur et al (2008) tested the effect of Se on nutrient levels in horse serum as affected by exercise. In horses treated with Se, the Ca and K levels decreased to levels lower than those of untreated controls before and after exercise.…”
Section: Introductionmentioning
confidence: 94%
“…Brummer et al (2013) observed a higher increase of GSH-Px activity in the blood of Se-supplemented horses after preliminary depletion of dietary Se in comparison with the animals regularly fed the Se-adequate diet, suggesting a good potential response of animals in the Sedeficient areas on the supplementation. Yur et al (2008) investigated the effect of intensive exercise on the element levels in horse serum. Among the macro-and micronutrients, only the Cu level and the Cu : Zn ratio was significantly increased, but the concentrations of Ca, K, Fe and Mg remained unchanged in intensively exercised horses.…”
Section: Introductionmentioning
confidence: 99%